THE NOMINEE SCHEME THROUGH THE LENS OF NEUTRAL SELF-MENTALITY AND UNEXPLAINED WEALTH - Whedy Prasetyo (Faculty of Economics and Business University of Mataram, 2025)
The phenomenon of increasing or possessing personal wealth without a clear source of income (unexplained wealth) often indicates criminal acts such as money laundering and corruption. This study aims to examine the nominee scheme from the perspective of neutral self-mentality as a mental character in preventing fraud. The research employs an interactive qualitative ethnographic approach, with the Bilik Literasi Community in Karanganyar Regency, Central Java, as the case study. The findings reveal that disguising ownership through the nominee scheme can be used to conceal illicit enrichment, including unreported assets and liabilities. The concept of neutral self-mentality in the fraud context not only involves wealth under an individual’s direct control but also indirect benefits that may elevate one’s lifestyle or standard of living. These insights provide a conceptual foundation for developing policies to prevent and combat money laundering and corruption.